A Development of the Turnitin System in Improving Plagiarism Detection for Islamic Religious Education Studies - Izi, Arilana Nur; Anggraini, Fadhilla Nangroe; Regita, Rahma; Rabiatuladawiyah, Rabiatuladawiyah (Universitas Muhammadiyah Surakarta, 2024)
The development of the turnitin system is used to minimize the similarities of words or sentences in writing articles or scientific papers. Turnitin, a widely used plagiarism detection software, provides a solution to identify and prevent plagiarism. However, it is important to adapt it to the context and specific needs of Islamic Religious Education studies at private Islamic universities. The proposed solution includes the integration of Turnitin with Islamic literature databases as well as the adjustment of detection algorithms to recognize religious texts. The existing problems include the impact of the turnitin system, development efforts and challenges, and problems related to plagiarism detection in the study of Islamic religious education. This type of research is called field research, which is to obtain data from direct research on the development of the turnitin system for improving plagiarism detection in Islamic religious education studies. The research is included in qualitative research with data collection techniques using direct observation in university libraries and supporting documents such as books, journals, and other sources. This Turnitin functions to check the level of similarity between sentences, words, paragraphs, and word structures of a written work with a written work made by someone or a student with someone else's previously published own. The development of the Turnitin system on each campus has its own advantages, but it also faces challenges from the side of students and the academic community related to maintaining academic integrity. This is essential for building trust, honesty, and creating a culture of excellence and professionalism while maintaining Turnitin's integrity. The biggest challenge faced is the emergence of the latest features provided by Turnitin, both turnitin draft coach and conventional turnitin.